SYSTEMATIC LITERATURE REVIEW OF THE DEVELOPMENT AND RESEARCH DIRECTIONS OF TECHNOLOGY INNOVATION-BASED TECHNOPRENEURSHIP - Rifanny Lysara Annastasya; Herbert Siregar (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2026)
The rapid development of digital technology has positioned technopreneurship as a strategic approach to strengthening innovation-driven economic competitiveness. However, research on technology innovation-based technopreneurship remains fragmented, and a systematic mapping of research trends and success determinants is still limited. This study aims to analyze research themes, identify key success factors, and highlight future research directions in technology innovation-based technopreneurship. The study employs a Systematic Literature Review (SLR) approach following the PRISMA guidelines to ensure transparency and replicability in the article selection process. A structured literature search was systematically conducted using the Scopus database, focusing on publications published between 2022 and 2025. The search, guided by predefined keywords, yielded a total of 200 articles for initial consideration. After applying predefined inclusion and exclusion criteria, a final corpus of five articles was identified and analyzed using a thematic analysis approach. The results reveal several dominant themes, including digital innovation, entrepreneurial capability development, startup ecosystem collaboration, and sustainability-oriented technopreneurship. The findings also indicate that the success of technopreneurship is influenced by the integration of individual competencies, digital leadership, and collaborative innovation ecosystems involving academia, industry, and government. This study contributes by providing a systematic mapping of recent technopreneurship research and identifying thematic patterns that shape technology-driven entrepreneurship in the digital era, offering academic insights and practical implications for strengthening innovation ecosystems.